Evolution and development of language for specific purposes texts - Sánchez Jiménez, David J. (Círculo de Lingüística Aplicada a la Comunicación, 2014)
Writing volves in society and so do kinds of text in a discourse community in specific ways. The disciplines involved in the analysis of these written texts follow these changes and explain these adjustments. This article reviews the idea of texts when discourse analysis began. Its objective is to look at how this concept has evolved within each discourse community through the several changes that have occurred in the society during the last few decades.